INCUBATION PUBLICATION MODEL FOR QUALITY IMPROVEMENT OF SCIENTIFIC BOOK: A CASE STUDY OF BOOKS ON FUNCTIONAL FOOD - Helmi, Rahmi Lestari; Ghani, Mochammad Wahyu (Record and Library Journal, 2019)
Background of the study: Lack of information on functional food ingredients in book form has encouraged LIPI Press to create an incubation scheme for scientific publications that can Accelerate the process of publishing scientific texts, roommates are always constrained by the halt of creative ideas from the authors.Purpose: The concept of implementing a scientific publication incubation scheme involves the process of transfer of knowledge and learning is a complex process and involves many parties, from the stage of ideas (ideation) until the book becomes available and is worth reading by the target reader.Method: The novelty aspect of research in the context of this activity is the implementation of the book publishing scheme (scientific), thus the need to establish an appropriate model.Findings: The concept of this the model emphasizes the aspects of knowledge management and communication between actors in publications items, namely, writers, experts, and publishers (editors).Conclusion: In this case, knowledge management will identify the most influential factors in supporting the incubation modeling of book publications so that the acceleration of the publication process can be optimized.